2021
DOI: 10.1037/cou0000536
|View full text |Cite
|
Sign up to set email alerts
|

Beyond symptom reduction: Development and validation of the Complementary Measure of Psychotherapy Outcome (COMPO).

Abstract: Most measures of psychotherapy outcome focus on symptomatic change. However, clients often report other changes through therapy, such as increased self-acceptance. This study reports on the development and validation of the Complementary Measure of Psychotherapy Outcome (COMPO) that assesses different areas of psychological functioning deemed important by clients and therapists. Items were written based on a literature review of client-reported change and feedback from experienced therapists. Exploratory facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Although Rogers’s definition of empathy implicates the therapist to move toward the client’s inner experience (Rogers, 1995), recent writings emphasize emotional coregulation where both the therapist and the client mutually influence each other (Fosha, 2001; Hilpert et al, 2020; Li & Kivlighan, 2020). For the client, learning to empathize with others (Chui et al, 2021; MacFarlane et al, 2017; Yalom, 2002), in this case to the therapist’s emotional experience, may be an important part of the psychotherapy process and also interpersonal learning and growth. A recent study also showed that mutual influence between therapist and client is associated with positive client outcome (Li, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although Rogers’s definition of empathy implicates the therapist to move toward the client’s inner experience (Rogers, 1995), recent writings emphasize emotional coregulation where both the therapist and the client mutually influence each other (Fosha, 2001; Hilpert et al, 2020; Li & Kivlighan, 2020). For the client, learning to empathize with others (Chui et al, 2021; MacFarlane et al, 2017; Yalom, 2002), in this case to the therapist’s emotional experience, may be an important part of the psychotherapy process and also interpersonal learning and growth. A recent study also showed that mutual influence between therapist and client is associated with positive client outcome (Li, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Psychological Functioning. The Complementary Measure of Psychotherapy Outcome (COMPO-12; Chui et al, 2021) is a self-report questionnaire consisting of 12 items that evaluates the psychological functioning deemed important by clients and therapists. A multi-step strategy was adopted for the translation of the COMPO-12 starting from the original English version developed by Chui (2021).…”
Section: Methodsmentioning
confidence: 99%
“…Posttreatment outcomes are typically assessed through clients completing standardized, psychometrically sound self-report measures before beginning psychotherapy and then again at its completion (and sometimes at intervals within treatment). Examples of such distal measures include the Beck Depression Inventory (Beck et al, 1961) and the Complementary Measure of Psychotherapy Outcome (Chui et al, 2021). In the vast majority of published randomized clinical trials comparing the relative efficacy of two or more treatment packages, the difference in distress between the start and the end of treatment constitutes the primary index of success.…”
Section: Distal Posttreatment Outcomesmentioning
confidence: 99%